Direct and indirect effects of caregiver social support on adolescent psychological outcomes in two South African AIDS-affected communities - Casale, M; Cluver, L; Crankshaw, T; Kuo, C; Lachman, JM; Wild, LG (Springer US, 2015)
Caregiver social support has been shown to be protective for caregiver mental health, parenting and child psychosocial outcomes. This is the first known analysis to quantitatively investigate the relationship between caregiver social support and adolescent psychosocial outcomes in HIV-endemic, resource–scarce Southern African communities. A cross-sectional household survey was conducted over 2009–2010 with 2,477 South African adolescents aged 10–17 and their adult caregivers (18 years or older) in one urban and one rural community in South Africa’s KwaZulu-Natal province. Adolescent adjustment was assessed using adult caregiver reports of the Strengths and Difficulties questionnaire (SDQ), which measures peer problems, hyperactivity, conduct problems, emotional symptoms and child prosocial behavior. Hierarchical linear regressions and multiple mediation analyses, using bootstrapping procedures, were conducted to assess for: (a) direct effects of more caregiver social support on better adolescent psychosocial wellbeing; and (b) indirect effects mediated by better parenting and caregiver mental health. Direct associations (p < .001), and indirect associations mediated through better parenting, were found for all adolescent outcomes. Findings reinforce the importance of social support components within parenting interventions but also point to scope for positive intervention on adolescent psychosocial wellbeing through the broader family social network.